Co-expression of NMDA-receptor subunits NR1, NR2A, and NR2B in dysplastic neurons of teratomas in patients with paraneoplastic NMDA-receptor-encephalitis: a retrospective clinico-pathology study of 159 patients - Jiang, Xin Yue; Lei, Song; Zhang, Le; Liu, Xu; Lin, Min Tao; Blümcke, Ingmar; Piao, Yue Shan; Zhou, Dong; Li, Jin Mei (Acta Neuropathologica Communications, 2020)
OBJECTIVE: To comprehensively describe the pathological features of neurons in patients with ovarian teratomas and paraneoplastic anti-NMDAR encephalitis (anti-NMDARE), emphasizing on NMDA-receptor expression and infiltrating lymphocytes. METHODS: A retrospective study was performed in a large series of 159 patients from the West China Hospital. We retrospectively identified 12 patients with paraneoplastic anti-NMDARE (11 case with ovarian teratomas and 1 case with mixed germ cell tumor), which were compared to 35 patients with teratomas and no encephalitis and to 147 patients with anti-NMDARE and no evidence for tumors. Patient history and outcome were reviewed from the clinical charts and compared between all three groups. Histopathological examination, including double-immunofluorescence of NMDAR subunits and IgG was performed in all teratoma tissues. Magnetic Luminex Assay Human Premixed Multi-Analyte Kit was performed to investigate cytokines profile of CSF. RESULTS: Patients with paraneoplastic anti-NMDARE had a more severe clinical presentation, i.e. they required more mechanical ventilation and intensive care (p < 0.001). Though immunotherapy was initiated earlier in this group, repeated intravenous immunoglobulin administration (IVIG) was more common (p = 0.002) and with higher cerebrospinal fluid (CSF) antibody titres (p = 0.004). Following tumor resection, the outcome did not differ between groups. A peculiar population of floating-frog like dysplastic neurons were observed only in teratomas of patients with paraneoplastic anti-NMDARE, co-expressing NR1, NR2A, NR2B subunits and IgG. Also, CD20 positive B-cells were more common in anti-NMDARE teratomas. In CSF of paraneoplastic anti-NMDARE patients, TNF-α, IL-10 and GM-CSF concentrations were higher than in negative symptom control and VEGF-A and IL-1a were lower than in anti-NMDARE patients (0.25 < p < 0.05). CONCLUSIONS: Patients with teratomas and paraneoplastic anti-NMDARE revealed a cellular population of dysplastic neurons co-expressing NMDAR subunits, which were the potential source of autoantigens triggering anti-NMDARE. Some inflammatory cytokines may be involved in pathogenesis of paraneoplastic anti-NMDARE.
CRIS-Team Scopus Importer:2020-08-21
Keywords: Chemokines; Cytokines; Dysplastic neurons; NMDA receptor; Teratoma